2018
DOI: 10.1093/nar/gky331
|View full text |Cite
|
Sign up to set email alerts
|

The longevity SNP rs2802292 uncovered: HSF1 activates stress-dependent expression of FOXO3 through an intronic enhancer

Abstract: The HSF and FOXO families of transcription factors play evolutionarily conserved roles in stress resistance and lifespan. In humans, the rs2802292 G-allele at FOXO3 locus has been associated with longevity in all human populations tested; moreover, its copy number correlated with reduced frequency of age-related diseases in centenarians. At the molecular level, the intronic rs2802292 G-allele correlated with increased expression of FOXO3, suggesting that FOXO3 intron 2 may represent a regulatory region. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 55 publications
3
44
1
Order By: Relevance
“…In carriers of the G allele of a longevity variant of FOXO3 , the FOXO3 gene was physically closer to its neighboring genes, and when exposed to stress, FOXO3 mRNA expression in lymphoblastoid cell lines derived from carriers increased more than in cell lines derived from non-carriers 62 . In line with those findings, another study showed that the same genetic variant has enhancer functions and that the G allele allows the creation of a novel transcription factor binding site, which induces FOXO3 mRNA expression in response to diverse stress stimuli 63 .…”
Section: Foxo3 and The Genetics Of Longevitymentioning
confidence: 57%
“…In carriers of the G allele of a longevity variant of FOXO3 , the FOXO3 gene was physically closer to its neighboring genes, and when exposed to stress, FOXO3 mRNA expression in lymphoblastoid cell lines derived from carriers increased more than in cell lines derived from non-carriers 62 . In line with those findings, another study showed that the same genetic variant has enhancer functions and that the G allele allows the creation of a novel transcription factor binding site, which induces FOXO3 mRNA expression in response to diverse stress stimuli 63 .…”
Section: Foxo3 and The Genetics Of Longevitymentioning
confidence: 57%
“…Furthermore, although the human PMAIP1 gene lacks a perfect HSE consensus sequence, HSF1 also exhibited increased binding to the HSE-like motif located in the intron in response to heat shock concomitant with upregulation of the gene expression. Transcription activation is usually associated with the binding of HSF1 to target gene promoters, although there are also reports showing the involvement of HSF1 in transcription regulation through intronic sequences [39][40][41]. This mode of regulation could rely on chromatin looping between intronic HSE and other regulatory sequences (e.g., enhancers) as it was shown by Grossi et al [40].…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies suggested the existence of an HSF1-FOXO3 axis in human cells that could be involved in stress response 203 . FOXO3 became physically connected, through chromatin looping, with 46 other genes on chromosome 6 thus forming an aging hub 199 .…”
Section: Igf-1 and Foxo3mentioning
confidence: 99%